Aerodynamic characteristics of two low aspect ratio rectangular wings at Mach 2 - Marson, G. B. (College of Aeronautics, 1956)
This note summarises the important results of a detailed experimental investigation into the flow and pressure distribution over two rectangular single wedge wings. The experiments were carried out .in the 9" x 9" supersonic tunnel at the College of Aeronautics, 6 at a Mach number of 2.0 and a Reynolds number of 2.5 x 10 per foot. Both wings had a chord of 3 inches and a total wedge angle of 6°. They had no real trailing edge, but were faired into a cylindrical support which could be rolled and pitched in the tunnel. Wing A was of 2 inch1span, giving an aspect ratio of 0.67. `Ting B was of 1 1/4 inch span, 0.42 aspect ratio. 132 pressure tappings 4 were spaced regularly over half of one surface of each wing, and up to 19 pressure readings could be taken simultaneously on vertical mercury manometers. models were pressure plotted at pitch angles of 0°, 2 1/2°, 5°, 7 1/2°, 10°, 15°, 20°, 25°, and 30°, and at all roll angles at intervals of 30°. Since each wing was symmetrical about the centreline, the complete pressure distribution over all surfaces at any roll angle Ø could he obtained from the readings taken on the one surface at Ø, 180°- Ø, 180° + Ø, and 360°- Ø. The pressure readings were then integrated to give the forces and moments on the complete wing… [cont.].